2022
DOI: 10.3390/antiox11020419
|View full text |Cite
|
Sign up to set email alerts
|

CoenzymeQ10 and Ischemic Preconditioning Potentially Prevent Tourniquet-Induced Ischemia/Reperfusion in Knee Arthroplasty, but Combined Pretreatment Possibly Neutralizes Their Beneficial Effects

Abstract: Tourniquet (TQ) use during total knee arthroplasty (TKA) induces ischemia/reperfusion (I/R) injury, resulting in mitochondrial dysfunction. This study aims to determine the effects of coenzyme Q10 (CoQ10) and ischemic preconditioning (IPC), either alone or in combination, on I/R-induced mitochondrial respiration alteration in peripheral blood mononuclear cells (PBMCs) and pain following TKA. Forty-four patients were allocated into four groups: control, CoQ10, IPC, and CoQ10 + IPC. CoQ10 dose was 300 mg/day for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…First, it was not investigated whether administration of DNase I or sivelestat before the onset of ischemia-reperfusion injury had an effect on rat skeletal muscle injury and exercise capacity, There are some studies that have shown that treatment with drugs prior to injury can reduce injury. 31 , 46 Second, the effect of other methods of administration, such as intraperitoneal injection, 47 on the therapeutic effect was not investigated. Finally, the possibility and efficacy of combined administration of DNase I and sivelestat were not discussed.…”
Section: Discussionmentioning
confidence: 99%
“…First, it was not investigated whether administration of DNase I or sivelestat before the onset of ischemia-reperfusion injury had an effect on rat skeletal muscle injury and exercise capacity, There are some studies that have shown that treatment with drugs prior to injury can reduce injury. 31 , 46 Second, the effect of other methods of administration, such as intraperitoneal injection, 47 on the therapeutic effect was not investigated. Finally, the possibility and efficacy of combined administration of DNase I and sivelestat were not discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Various combinations of effects are known, for example, when a chemical effect is manifested by a physical one or vice versa. The preconditioning effect is known at the level of the organism [88,89], physiology [90,91], tissues [8,92], cells [93], and biological residues, liquids, aqueous colloids, and solutions [94,95], and, as shown in this study, in water.…”
Section: Influence Of Magnetic Field and Mechanical Action By Pipetti...mentioning
confidence: 91%
“…After centrifugation, the PBMC ring at the Ficoll/plasma interface was collected and washed twice with PBS solution. The pallet was submitted for cell counting using a haemocytometer technique following the final centrifugation at 1000 g for 10 min 14 …”
Section: Methodsmentioning
confidence: 99%
“…The EDTA‐coated tube was used to collect blood, and a Ficoll density gradient centrifugation was used to separate the PBMCs 14 . Peripheral Blood Mononuclear Cells were used to measure cell death and mitochondrial function including mitochondrial respiration, mitochondrial oxidative stress and mitochondrial mass.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation